Transaksi Jual-beli dalam Bentuk Khusus - Nanang Qosim; Vita Firdausiyah (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2018)
Abstract: Sale-purchase order in Islamic fiqih is called as-salam or as-salaf. Terminologically, the fiqh scholars issue it by: Offer of goods which the delivery is postponed, or sell goods that are distinct with early payment of capital, while the goods are the day of payment.Bay 'al-wafa' Etymologically, al-bay 'means buying and selling, and al-wafa' the meaning of repayment / settlement of obligations. Bay'al-wafa 'is a form of transaction (akad) which emerged in Central Asia (Bukhara and Balkh) in the middle of the 5th century Hijriyah and spread to the Middle East.The word ihtikar The origin of the word hakara which means az-zulm (persecution) and isa'ah al-mu'asyarah (social damage). With ihtakara scales, yahtakiru, ihtikar, this word means stockpiling to wait for soaring prices Keywords: Sale-purchase Orders, Bay 'al-Wafa' and Ihtikar